Stylized caustics: Progressive rendering of animated caustics - Günther, Tobias; Rohmer, Kai; Roessl, Christian; Grosch, Thorsten; Theisel, Holger (Computer Graphics Forum, 2016)
In recent years, much work was devoted to the design of light editing methods such as relighting and light path editing. So far, little work addressed the target-based manipulation and animation of caustics, for instance to a differently-shaped caustic, text or an image. The aim of this work is the animation of caustics by blending towards a given target irradiance distribution. This enables an artist to coherently change appearance and style of caustics, e.g., for marketing applications and visual effects. Generating a smooth animation is nontrivial, as photon density and caustic structure may change significantly. Our method is based on the efficient solution of a discrete assignment problem that incorporates constraints appropriate to make intermediate blends plausibly resemble caustics. The algorithm generates temporally coherent results that are rendered with stochastic progressive photon mapping. We demonstrate our system in a number of scenes and show blends as well as a key frame animation.
CRIS-Team Scopus Importer:2020-09-23